Characterization of Academic Procrastination in Peruvian University Students - Duda-Macera, Beatriz (2022)
Aims. This study aimed to understand the characteristics associated with academic procrastination in engineering students at a private university in Lima. The theoretical bases were Barkley’s Theory of Executive Functions and Bandura’s Theory of Self-Efficacy. Method. A qualitative method combined with a phenomenological design was used to understand the research topic from the participant’s point of view. Semi-structured interviews were conducted with ten students who attended individual coaching sessions and tended to have low grades and procrastinate. A thematic analysis was conducted to identify, organize and recognize patterns from a deep reading of the data to understand the research topic. Results. The results show that students have not been able to incorporate study habits, which leads them to postpone their tasks. In addition, they are distracted by the use of technology and have anxiety and stress. Conclusions. Nowadays, academic procrastination is understood from a more comprehensive perspective that considers executive functioning, supported by scientific discoveries about the human brain.